2018
DOI: 10.1002/1878-0261.12399
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐driven paracrine osteopontin/integrin αvβ3 signaling promotes pancreatic cancer cell epithelial–mesenchymal transition and cancer stem cell‐like properties by modulating forkhead box protein M1

Abstract: Pancreatic stellate cells (PSCs), a key component of the tumor microenvironment, contribute to tumor invasion, metastasis, and chemoresistance. Osteopontin (OPN), a phosphorylated glycoprotein, is overexpressed in pancreatic cancer. However, OPN expression in PSCs and its potential roles in tumor–stroma interactions remain unclear. The present study first showed that OPN is highly expressed and secreted in activated PSCs driven by hypoxia, and this process is in a ROS‐dependent manner; in addition, OPN was sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 50 publications
4
51
0
1
Order By: Relevance
“…Many studies have revealed that FOXM1, a carcinogenic transcriptional factor, has a critical function in the pathogenesis of various cancers, including liver cancer [43,44]. However, the FOXM1-related upstream regulatory events in LCSCs are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed that FOXM1, a carcinogenic transcriptional factor, has a critical function in the pathogenesis of various cancers, including liver cancer [43,44]. However, the FOXM1-related upstream regulatory events in LCSCs are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Cao et al. reported that hypoxia‐driven paracrine osteopontin/integrin αvβ3 signaling promoted pancreatic cancer cell epithelial‐mesenchymal transition and cancer stem cell‐like properties by modulating FOXM1. Deng et al.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The molecular mechanism and therapeutic strategies of PC have been continuously studied. 3,4 Therefore, it is of great significance for us to determine the molecular mechanism of PC and find more novel biomarkers for PC to contribute to the developmental, preventive and therapeutic strategies for PC.…”
Section: Introductionmentioning
confidence: 99%